Patterns in Coastal Migration and Stock Structure of Capelin ( Mallotus villosus ) - Nakashima, Brian S. (Canadian Journal of Fisheries and Aquatic Sciences, 1992)
Approximately 57 500 mature capelin (Mallotus villosus) were tagged with external tags from 1983 to 1988 along the southeast and east coasts of Newfoundland to determine inshore migration patterns and to reexamine the current belief that two separate capelin stocks spawn on east coast beaches. Capelin released in a particular bay were recaptured from the same bay or locations further north. Upstream migration using the Labrador Current was hypothesized as a directional clue to the prespawning migration. Capelin caught in one stock area were recaptured in another area, indicating that mature capelin from the Northeast Newfoundland – Labrador and Northern Grand Bank – Avalon stocks mix and migrate north together. The distribution and mixture of pre-spawning fish inshore as described by tag returns have implications on how capelin resources should be surveyed, assessed, and managed.